Ethanol production from cassava stem using Saccharomyces cerevisiae TISTR 5339 through simultaneous saccharification and fermentation - Niyomvong, Nanthavut (Agriculture and Natural Resources, 2019)
The stems of cassava (Manihot esculenta Crantz) are agro-waste that can provide an alternative source for the production of glucose as a bioenergy resource. The potential was studied of cassava stem as a raw material in the production of ethanol, through a simultaneous saccharification and fermentation process using Saccharomyces cerevisiae TISTR 5339. Steam explosion was applied as the pretreatment process to break the structure of cellulose, hemicellulose and lignin. The results indicated that after the pretreatment process at 210°C for 5 min, a higher yield of α-cellulose (91.06%) was obtained at a significance level of 95%. Experimental designs were used to optimize the appropriate nutrients for ethanol production. The maximum achieved value of ethanol concentration at 8.77% (weight per volume; w/v) corresponded well with the predicted value of 8.76% (w/v), under the optimized conditions at a solid loading of 20% and yeast extract of 2.05%.